PENGARUH PERHATIAN ORANG TUA DAN KONSEP DIRI TERHADAP PRESTASI BELAJAR SISWA MATA PELAJARAN PRODUKTIF AKUNTANSI PADA SMK DI KOTA PAYAKUMBUH - Yuli Hendriani; Bustari Muchtar (Program Magister Pendidikan Ekonomi (S2), 2015)
This study aimed to analyze (1) the effect of parents attention to student self concept (2) the effect of parents attention to student achievement (3) the effect of self concept to student achievement. This research is associative. The study population was all of the 10th of SMK in Payakumbuh registrated on 2013/2014 of academic year, totaling 157 people. The sampling technique was done by proportional random sampling with 113 people of sample size. Data analysis technique used path analysis and hypothesis testing used the t test and F test. The results showed that: (1) parents attention significantly influence the SMK students of Payakumbuh in self concept of accounting subjects (2) parents attention significantly influence the Payakumbuh student’s achievement on Accounting subject (3) self concept significantly influence the Payakumbuh student’s achievement on Accounting subject. Based on these results, it is recommended to all parents to totally give the attention for their child so that student achievement can be improved., and to all of 1oth grade students of SMK in Payakumbuh to improve their self concept to get the expected learning achievement.Key word: parents attention, self concept, achievement of learning